Working with water in medieval Europe : technology and resource-use - Squatriti, Paolo, 1963- (Technology and change in history, 2000)
A comprehensive survey of the techniques people used to harness, and defend themselves from, water in Western Christendom from 500-1500, each chapter of this volume sets the technologies of fishing, land drainage, irrigation, flood control, and water supply within a social and cultural context.